Liberalized Versus Strict Cow's Milk Elimination for the Treatment of Children with Eosinophilic Esophagitis. Issue 2 (4th July 2018) - Teoh, Timothy; Mill, Christopher; Chan, Edmond; Zimmer, Preeti; Avinashi, Vishal
Abstract: Objectives: Cow's milk is a commonly implicated trigger in eosinophilic esophagitis (EoE). Exclusive cow's milk avoidance has been reported previously, but the degree of elimination required for remission is unclear. Strict food avoidance may confer a risk of developing immunoglobulin E (IgE)-mediated allergy. The goal of this study was to evaluate the effectiveness of cow's milk elimination (CME) in children with EoE and compare responses of strict and liberalized CME diets. Methods: Children (≤16 years) diagnosed with EoE who were treated with exclusive CME diets were evaluated clinically and histologically. Strict diets eliminated all milk products, including 'may-contain' and baked milk goods. Liberalized diets eliminated obvious sources including milk, cheese, yogurt, cream-based products but permitted foods with traces of milk and baked goods. Results: Cow's milk elimination induced histological remission of <15 eosinophils per high-powered field in 18 of 31 children (58%) and complete remission in 23%. Overall, 77% had decreased eosinophils with this single intervention. Symptoms were improved in 90% of patients, regardless of histologic response. A liberalized (n=7) CME diet was associated with a nonsignificantly lower response compared with strict (n=24) elimination (29% versus 67%, P =0.099). Eight responders to strict elimination were transitioned to a liberalized diet; 63% maintained remission. Conclusion: Cow's milk elimination induced clinicopathological remission in a majority of patients with EoE, supporting its use as a first-line intervention. Liberalized CME allows dietary freedom and may prevent subsequent development of anaphylactic milk allergy but may be inferior to strict CME for improving EoE.